Influencia de las representaciones sociales sexistas en las relaciones de genero en adolescentes de la i.e. leoncio prado. 2014 - Laiza Vidal, Katerine Karina (2014)
The gender approach is the guiding this study, which gives me a look of equity and respect for human rights during the establishment of gender relations among / as teenagers secondary level educational institution Leoncio Prado. This study sought to know which are the basis for the exercise of violence in gender relations that are adding to the gap between female and male. The importance of the study is that the study highlights the need to identify what and how much affect sexist gender relations during adolescence social representations since at this stage the capacity will increase to model social interaction . Through this thesis is intended to reflect some of the social representations that / the 120 teens surveyed / as have about violence and relationships, thus confirming distortions thereof, which may lead them to configure a list of non-egalitarian couples, play stereotypical roles socially legitimized as male or female and tolerate abusive situations, since they do not recognize or minimize certain signs of violence.